Additive- and Catalyst-free Deoxygenative Reduction of Amides and Imides to Amines with Ammonia Borane - Xu, Ke; Zhou, Min-Jie; Liu, Xinrui; Chen, Guofei; Xie, Yinjun (Synlett, 2025)
The reduction of carbonyl compounds is one of the most fundamental and useful transformations in synthetic chemistry. However, due to the high resonance stability of the amide group, reducing amide compounds is difficult and always requires harsh reductants and/or additional catalysts/additives. In this report, we describe a catalyst-free, additive-free protocol for the deoxygenative reduction of amides using ammonia borane as a mild reductant. Tertiary, secondary, and primary amides, as well as challenging imides can be reduced to the corresponding amines under these conditions. Additionally, the transformation performed well in open air, making the method more practical.
Keywords: Amide; Imide; Deoxygenative reduction; Amines; Ammonia borane